Recent tools and techniques of BIM-Based Augmented Reality: A systematic review. (October 2021) - Sidani, Adeeb; Matoseiro Dinis, Fábio; Duarte, Joana; Sanhudo, Luís; Calvetti, Diego; Santos Baptista, João; Poças Martins, João; Soeiro, Alfredo
Abstract: The Architecture, Engineering, Construction, and Operations (AECO) sector has always been recognised as a competitive and complex sector. In recent years, increased demands on construction projects in different domains such as safety, energy, time and cost management have pushed the industry towards new tools and methods, including more efficient use of digital technologies. Among the multiple available digital solutions, Building Information Modelling (BIM) is quickly positioning itself as a fundamental methodology, with its practices and tools being increasingly deployed. However, the remaining challenges to BIM adoption provide an opportunity for the development of supporting tools. The present article analyses Augmented Reality (AR) as such a tool. A systematic review was conducted to examine previous studies in the field of BIM-based AR, shedding light on the integration of this technology in the AECO sector. A list of questions was presented and answered to understand this technology's role in multiple aspects, from its main stage and field of application to the targeted stakeholders. The applied review methodology is based on PRISMA-P. The databases exploited to search for eligible articles were Scopus, Academic Search Ultimate, Current Content, Web of Science, and ScienceDirect. From an initial cohort of 671 articles, 24 were selected for analysis. Additionally, a comparison between AR and Virtual Reality (VR) applications is presented. This review shows that AR implementation is far from its desired state, showing several limitations such as connection and localisation problems, lack of non-geometric information, and other challenges in using AR techniques in the construction site, (e.g., marker-based AR). Graphical abstract: Image 1 Highlights: Augmented Reality (AR) adds to the real world, projecting information on top of what the user already sees. BIM-based AR is a promising new approach to improve construction quality. BIM-based AR is aiding task completion, reducing errors, shortening schedule, reducing rework, lowering costs. AR tools increases the project's efficiency, safety, collaboration, inspection, and monitoring. AR tools provides new ways to design and understand and study structures and designs. Although AR has not yet reached its full potential in construction, it is showing rapid progress.